Post-polio Syndrome: More Than Just a Lower Motor Neuron Disease - Li Hi Shing, Stacey; Chipika, Rangariroyashe H.; Finegan, Eoin; Murray, Deirdre; Hardiman, Orla; Bede, Peter (Frontiers in Neurology, 2019)
Post-polio syndrome (PPS) is a neurological condition that affects polio survivors decades after their initial infection. Despite its high prevalence, the aetiology of PPS remains elusive, mechanisms of progression are poorly understood and the condition is notoriously under-researched. While motor dysfunction is a hallmark feature of the condition, generalised fatigue, sleep disturbance, decreased endurance, neuropsychological deficits, sensory symptoms and chronic pain are also often reported and have considerable quality of life implications in PPS. The non-motor aspects of PPS are particularly challenging to evaluate, quantify and treat. Generalised fatigue is one of the most distressing symptoms of PPS and is likely to be multifactorial due to weight-gain, respiratory compromise, poor sleep and polypharmacy. No validated diagnostic, monitoring or prognostic markers have been developed in PPS to date and the mainstay of therapy centres on symptomatic relief and individualised rehabilitation strategies such as energy conservation and muscle strengthening exercise regimes. Despite a number of large clinical trials in PPS, no effective disease-modifying pharmacological treatments are currently available.